Accuracy of Calf Circumference Measurement, SARC-F Questionnaire, and Ishii's Score for Screening Stroke-Related Sarcopenia - Yao, Ruihong; Yao, Liqing; Yuan, Changli; Gao, Bu-Lang (Frontiers in Neurology, 2022)
Objective: To investigate the accuracy of sarcopenia diagnosis in stroke patients using calf circumference (CC), SARC-F questionnaire, and Ishii’s score in comparison with the Asian Working Group for Sarcopenia 2019 ( AWGS) sarcopenia diagnostic criteria. Materials and Methods: In this cross-sectional study, a total of 364 consecutive stroke patients were enrolled and evaluated with the CC measurement, SARC-F questionnaire, and Ishii’s score. The diagnostic accuracy was analyzed. Results: Based on the AWGS criteria, Sarcopenia was present in 180 (49.5%) patients, with an age range of 49-74 (mean 63±14.7) years. In all patients, the cutoff value of CC in the accuracy of diagnosing sarcopenia was 30.5 cm, with an AUC of 0.85, sensitivity of 81.8%, specificity of 90.1%, Kappa value of 0.72, and Youden index of 0.72. In the accuracy of diagnosing sarcopenia in all patients, the Ishii’s score had a cutoff value of 118, an AUC of 0.78, sensitivity of 90.1%, specificity of 36.0%, Kappa value of 0.4, and Youden index of 0.55. For accuracy of diagnosing sarcopenia, the SARC-F questionnaire had a cutoff value of 5, an AUC 0f 0.731, sensitivity of 94.7%, specificity of 40%, Kappa value of 0.34, and Youden index of 0.41. Conclusions: Based on the AWGS criteria, calf circumference measurement has the optimal performance in screening stroke-related sarcopenia compared with the SARC-F questionnaire and Ishii’s score. In stroke patients, the cutoff value of calf circumference for sarcopenia is less than 31 cm in males and 30cm in females, and with an AUC of 0.85.